Enhanced international prognostic index in Japanese patients with diffuse large B-cell lymphoma. (2016) - Nakaya, Aya; Fujita, Shinya; Satake, Atsushi; Nakanishi, Takahisa; Azuma, Yoshiko; Tsubokura, Yukie; Hotta, Masaaki; Yoshimura, Hideaki; Ishii, Kazuyoshi; Ito, Tomoki; Nomura, Shosaku
Abstract: To evaluate the National Comprehensive Cancer Network (NCCN) International Prognostic Index (IPI), we analyzed 284 patients treated with the combination of rituximab, cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in our institution in Japan. Their 5-year overall survival (OS) by risk level was 80.7%, 74.8%, 55.4% and 67.5% ( P =0.005); and their 5-year progression-free survival (PFS) was 76.8%, 78.6%, 63.7% and 58.3% ( P =0.0722). The NCCN-IPI is a simple scale that uses conventional clinical factors, but did not reflect survival in our cohort. The NCCN-IPI may require further evaluation for different regions and ethnicities before adopting it for routine clinical use. Highlights: The NCCN-IPI is developed to predict survival in the rituximab era. The NCCN-IPI failed to predict survival in our cohort. The NCCN-IPI may require further evaluation before routine clinical use.